An anthology of living religions - Fisher, Mary Pat, 1943-; Bailey, Lee Worth (Upper Saddle River, N.J. : Prentice Hall, 2000)
[TofC cont] -- Confucianism: Confucian classics; Scholars' commentaries; Living confucianism -- Taoism: Traditional canon; Later developments -- Judaism: Jewish Bible, Tanakh; Prophets; Evolving theology and spirituality -- Christianity: Jesus the Christ; Early non-canonical texts -- Islam: Prophet Muhammad; Sufi mysticism -- Sikhism: Daily prayers; Dasam Granth -- New Religious movements: Old religions in new skins; Nature spirituality -- Interfaith movement: Oneness of religions; Interfaith initiatives; Celebration of religions. This anthology of readings from the major world religions draws together excerpts from key scriptures, later writings, and contemporary articles to provide a ... sense of each faith. [The] book gives each religion the opportunity to explain itself, its beliefs and relevance in today's world in its own terms. With the assistance of an international team of highly-respected specialists, the authors have selected a variety of ... excerpts which provide ... insight into today's living religions and the profound impact these religions have on the lives of countless people around the world. -Back cover.
Religious response: Comparative study of religion, Interpreting the sacred / W.E. Paden; Phenomenology of religions, Sacredness of nature and cosmic religion / M. Eliade; Materialistic perspectives on religion, The future of an illusion / S. Freud, Religion as the opium of the people / K. Marx, God is dead / F. Nietzsche; Religious points of view, The oneness of divine / A. Heschel, New politheeism / D. Miller, Ground of being / T. Tulku; Worship, symbol, and myth, Mandalas, deity unfolding in the world / C.G. Jung, The hero with a thousand faces / J. Campbell; Women and feminine in religion, When God was a woman / M. Stone; Need for religion today, Lost dimension in religion / P. Tillich -- Indigenous sacred ways: African sacred ways, Talking drum, African sacred liturgy / G. Niangoran-Bouah; Native North American sacred ways, The mountain has spirit / Southwest indigenous peoples, Seeing with a native eye / B. Toelken -- Hinduism: Sruti text 62, Hymn to Agnit, God of fire / R. Vedas; Songs of the saints; Modern texts; contemporary issues -- Jainism: Teachings of Mahavir; Harmlessness; Perfection of the soul; Renunciation -- Buddhism: Awakened one; Theravada; [Cont. in Annot.]
Includes bibliographical references and index.
Keywords: Religions; Religions -- History -- Sources